Reminiscences - Tagore, Rabindranath 1861-1941. (London: Macmillan, 1966)
Autobiographical.
Reprint of the 1917 ed.
Keywords: Tagore, Rabindranath, -- 1861-1941.; Biography. -- 19th century; Biography. -- 20th century